Colostral immunity as an analytical factor in predicting the development of acute respiratory viral infections in calves - E. N. Shilova; A. P. Poryvaeva; E. V. Pechura; L. V. Khalturina (Ветеринария сегодня, 2021)
To reduce the incidence of acute respiratory viral infections in cattle, routine vaccination of mother cows is carried out. There is a direct dependence of the passive immunity level in calves on the vaccination efficacy in cows. The paper presents the results of a study of colostral immunity in calves and post-vaccination immunity in cows against the agents of acute respiratory viral infections in agricultural facilities located on the territory of the Ural and Volga Federal Districts. In the farms under study (n = 10), cattle are vaccinated with inactivated vaccines: “COMBOVAC” and “COMBOVAC-R” (OOO Vetbiokhim, Russia), “HIPRABOVIS® 4” (Laboratorios Hipra, S. A., Spain). The study of postvaccinal immunity level in cows showed that the levels of antibodies to infectious bovine rhinotracheitis virus (5.3–8.0 log2), bovine viral diarrhea virus (3.5–4.8 log2), bovine parainfluenza-3 virus (6.8–8.5 log2) and bovine respiratory syncytial virus (4.2-4.5 log2) in cattle confer protection. When evaluating the results of serological diagnostics of passive immunity in calves to acute respiratory viral infections, it was found that the level of colostral antibodies in them is lower than the level of post-vaccination antibodies in cows: to infectious bovine rhinotracheitis virus by 34.2–58.8%; to bovine diarrhea virus by 37.5–45.0%; to bovine parainfluenza-3 virus by 14.7–35.4 and to bovine respiratory syncytial virus by 23.5-42.2%. To ensure epizootic favourable situation, it is proposed to adjust the schedules of vaccination against bovine diseases in herds, infected by acute respiratory viral infections for dairy farms under study.